The Arabidopsis PLAT domain protein1 is critically involved in abiotic stress tolerance - Hyun, Tae Kyung; van der Graaff, Eric; Albacete, Alfonso; Eom, Seung Hee; Großkinsky, Dominik K; Böhm, Hannah; Janschek, Ursula; Rim, Yeonggil; Ali, Walid Wahid; Kim, Soo Young; Roitsch, Thomas (PloS one, 2014)
Despite the completion of the Arabidopsis genome sequence, for only a relatively low percentage of the encoded proteins experimental evidence concerning their function is available. Plant proteins that harbour a single PLAT (Polycystin, Lipoxygenase, Alpha-toxin and Triacylglycerol lipase) domain and belong to the PLAT-plant-stress protein family are ubiquitously present in monocot and dicots. However, the function of PLAT-plant-stress proteins is still poorly understood. Therefore, we have assessed the function of the uncharacterised Arabidopsis PLAT-plant-stress family members through a combination of functional genetic and physiological approaches. PLAT1 overexpression conferred increased abiotic stress tolerance, including cold, drought and salt stress, while loss-of-function resulted in opposite effects on abiotic stress tolerance. Strikingly, PLAT1 promoted growth under non-stressed conditions. Abiotic stress treatments induced PLAT1 expression and caused expansion of its expression domain. The ABF/ABRE transcription factors, which are positive mediators of abscisic acid signalling, activate PLAT1 promoter activity in transactivation assays and directly bind to the ABRE elements located in this promoter in electrophoretic mobility shift assays. This suggests that PLAT1 represents a novel downstream target of the abscisic acid signalling pathway. Thus, we showed that PLAT1 critically functions as positive regulator of abiotic stress tolerance, but also is involved in regulating plant growth, and thereby assigned a function to this previously uncharacterised PLAT domain protein. The functional data obtained for PLAT1 support that PLAT-plant-stress proteins in general could be promising targets for improving abiotic stress tolerance without yield penalty.
Keywords: signální transdukce; fyziologický stres; Salts; Signal Transduction; proteiny huseníčku; Promoter Regions, Genetic; Phylogeny; soli; Protein Binding; Electrophoretic Mobility Shift Assay; nízká teplota; Arabidopsis Proteins; regulace genové exprese u rostlin; Cold Temperature; Gene Expression Regulation, Plant; retardační test; Stress, Physiological; transkripční faktory bZIP; Arabidopsis; tunikamycin; Transcriptional Activation; aktivace transkripce; Abscisic Acid; Tunicamycin; Basic-Leucine Zipper Transcription Factors; stres endoplazmatického retikula; Endoplasmic Reticulum Stress; fylogeneze; vazba proteinů; kyselina abscisová; období sucha; Droughts; promotorové oblasti (genetika)